2018
DOI: 10.1038/s41598-018-25168-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV and Type 2 diabetes on Gut Microbiota Diversity, Tryptophan Catabolism and Endothelial Dysfunction

Abstract: HIV infection and type 2 diabetes are associated with altered gut microbiota, chronic inflammation, and increased cardiovascular risk. We aimed to investigate the combined effect of these diseases on gut microbiota composition and related metabolites, and a potential relation to endothelial dysfunction in individuals with HIV-infection only (n = 23), diabetes only (n = 16) or both conditions (n = 21), as well as controls (n = 24). Fecal microbiota was analyzed by Illumina sequencing of the 16 S rRNA gene. Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 50 publications
3
38
3
Order By: Relevance
“…Such studies should include the evaluation of the functions of tryptophan metabolites resulting from tryptophan-gut-microbiota interactions on the causes and prevention of human diseases. 102 106 …”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Such studies should include the evaluation of the functions of tryptophan metabolites resulting from tryptophan-gut-microbiota interactions on the causes and prevention of human diseases. 102 106 …”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…In addition, among women with or at high risk for HIV infection, diabetes is associated with gut microbiota and plasma metabolites alteration; several metabolites in tryptophan catabolism, as well as the KYN/TRP ratio were higher in women with diabetes compared with those without diabetes [40]. Another study indicated that the combination of HIV infection and type 2 diabetes was associated with reduced gut microbiota diversity and increased plasma KYN/TRP ratio [68]. Nevertheless, for HIV comorbidities, the potential contributions and impacts of gut microbiota need to be further explored in large prospective studies powered for clinical end points.…”
Section: Tryptophan Catabolismmentioning
confidence: 99%
“…In contrast to the global health improvement occurring in people living with HIV (PLWH) receiving antiretroviral therapy (ART), gut damage persists and translocation of microbial products from the gut lumen into the circulation contributes to inflammatory non-AIDS comorbidities [5]. Microbial translocation is one of the main drivers for the development of such comorbidities including cardiovascular disease, depression and cancer in ARTtreated PLWH [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%